Back to Bentham: Should we? Large-scale comparison of decision versus experienced utility for income-leisure preferences - Alpaslan Akay; Olivier Bargain; H. Xavier Jara (University of Essex, Institute for Social and Economic Research (ISER), 2015)
Subjective well-being (SWB) is increasingly used as a way to measure individual well-being. Interpreted as "experienced utility", it has been compared to "decision utility" using specific experiments (Kahneman et al., 1997) or stated preferences (Benjamin et al. 2012). We suggest here an original large-scale comparison between ordinal preferences elicited from SWB data and those inferred from actual choices (revealed preferences). Precisely, we focus on income-leisure preferences, closely associated to redistributive policies. We compare indifference curves consistent with income-leisure subjective satisfaction with those derived from actual labor supply choices, on the same panel of British households. Results show striking similarities between these measures on average, reflecting that overall, people's decision are not inconsistent with SWB maximization. Yet, the shape of individual preferences differ across approaches when looking at specific subpopulations. We investigate these differences and test for potential explanatory channels, particularly the roles of constraints and of individual "errors" related to aspirations, expectations or focusing illusion. We draw implications of our results for welfare analysis and policy evaluation.
Keywords: C90; D63; 330; decision utility; experienced utility; labor supply; subjective well-being